ANALISA DAN PERANCANGAN SISTEM INFORMASI PENJUALAN KERAJINAN TEMBAGA DAN KUNINGAN BERBASIS WEBSITE PADA GUNDUL ART BOYOLALI: ANALYSIS AND DESIGN OF INFORMATIONS SYSTEMS SALES OF COPPER AND BRASS CRAFTS IN GUNDUL ART BOYOLALI - Via Avelia Khoirul Nisa; Niken Retnowati; Rizka Safitri L; Agustinus Suradi (Journal of Computer Science and Technology, 2023)
Gundul Art is one of shop selling various kinds of copper and brass handicrafts in Cepogo, Boyolali. So far, the media for conveying information used by Gundul Art is still very simple, namely only through Instagram, so that marketing of products and services is felt to be less than optimal. The transaction system on Gundul Art itself is also still manual, where you use email to find out the model, price and size of the craft being made, and then the order must also come directly to the craftsman, so it is very inefficient. Based on the background above, a web-based copper and brass sales information system was created for Gundul Art Boyolali. It is hoped that this system will make transactions and marketing at Gundul Art more effective and efficient. Furthermore, the system that has been created with SWOT analysis will also be analyzed to avoid mistakes in carrying out company operations in utilizing the newly created website. Where SWOT analysis is a planning technique in evaluating strengths, weaknesses, opportunities and threats in a company. The result of this research is a web-based copper and brass sales information system for Gundul Art Boyolali, where with the existing system, the marketing of Gundul Art is expanding. In addition, from the SWOT analysis, it was found that internally Gundul Art's strengths are greater than its weaknesses, while externally the opportunities are greater than the threats. Apart from that, the SWOT analysis also resulted in an IFAS-EFAS value in quadrant I, namely the application of an aggressive strategy, where the implementation of this strategy was to increase promotional media, increase production capacity as stock and rely on product quality with new innovations.